2017
DOI: 10.1097/mjt.0000000000000526
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Acetaminophen for Renal Colic in the Emergency Department: Where Do We Stand?

Abstract: In this meta-analysis, we found that data on the efficacy, safety, opioid-sparing effects, and cost-benefit analyses of IV APAP for renal colic were weak. Based on the available data, IV APAP should not be considered as an alternative to opioids or nonsteroidal anti-inflammatory drugs for the primary management of renal colic in the ED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 26 publications
2
7
0
Order By: Relevance
“…In the era of increasing opioid use, this benefit could have a significant clinical and public health relevance that should be carefully considered. Our study showed that tramadol is superior to acetaminophen in decreasing pain intensity and the need for rescue morphine treatment, suggesting the weak opioid‐sparing effects of acetaminophen alone as concluded by recent meta‐analysis . Indeed, in the past 2 decades, evidence‐based multimodal opiate‐sparing analgesia has become increasingly widespread in different clinical settings.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…In the era of increasing opioid use, this benefit could have a significant clinical and public health relevance that should be carefully considered. Our study showed that tramadol is superior to acetaminophen in decreasing pain intensity and the need for rescue morphine treatment, suggesting the weak opioid‐sparing effects of acetaminophen alone as concluded by recent meta‐analysis . Indeed, in the past 2 decades, evidence‐based multimodal opiate‐sparing analgesia has become increasingly widespread in different clinical settings.…”
Section: Discussionsupporting
confidence: 60%
“…Our study showed that tramadol is superior to acetaminophen in decreasing pain intensity and the need for rescue morphine treatment, suggesting the weak opioid-sparing effects of acetaminophen alone as concluded by recent meta-analysis. 24,25 Indeed, in the past 2 decades, evidence-based multimodal opiatesparing analgesia has become increasingly widespread in different clinical settings. The concept is to combine drugs from different classes to provide a better analgesia at reduced doses of individual agents with an opiatesparing effect.…”
Section: Discussionmentioning
confidence: 99%
“…Since 2015, the research program produced 14 peer-reviewed publications. All publications were based on pharmacy practice or use of pharmacotherapy, which included 7 case reports (50%), 31 -39 4 structured evidence-based reviews (28.5%), 38 -41 1 original prospective randomized double-blind, placebo-controlled trial (7.1%), 42 one meta-analysis (7.1%), 43 and 1 original retrospective cohort study (7.1%). 30 Six pharmacy residents from 5 different classes and 7 pharmacy students were first, second, or third authors on the publications.…”
Section: Resultsmentioning
confidence: 99%
“…To compare the IV-PC with morphine for the management of acute renal colic pain, Bektas et al conducted a doubleblind, placebo-controlled clinical trial and showed that the efficacy of both IV-PC and morphine was similar (12). In a systematic review and meta-analysis by Sin et al, the safety, efficacy, cost-benefits and opioid-sparing effects of IV-PC in patients with renal colic were determined and demonstrated that IV-PC was weaker in the pain reduction than opioids or nonsteroidal anti-inflammatory drugs (20). Additionally, different studies evaluated the side effects of PC versus KET following different procedures.…”
Section: Discussionmentioning
confidence: 99%